Strategi Pemerintah Gampong dalam Meningkatkan Kesadaran Masyarakat tentang Bahaya Covid-19 di Gampong Aneuk Glee, Indrapuri, Aceh Besar, Indonesia - Munawarah, Risfaton; Fakhruddin (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) Universitas Islam Negeri Ar-Raniry Banda Aceh, 2021)
The purpose of this research is to provide education to increase public awareness of the dangers of covid-19. In addition, this study found the importance of raising public awareness to adhere to health protocols to avoid the dangers of Covid-19. The research target is the government of Gampong Aneuk Glee, Indrapuri Sub District. This study uses a qualitative method that aims to determine the Gampong government’s strategy in increasing public awareness about the dangers of Covid-19. The data was obtained through three data collection methods, including interviews, observation, and analysis. The results showed that the Gampong Aneuk Glee government had carried out many strategies in increasing public awareness, such as placing banners and appealing to the public about the dangers of Covid-19. It is intended to increase public awareness regarding the dangers of Covid-19 optimally.